2013
DOI: 10.1021/la401679u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid and Fatty Acid Composition of Phospholipid Vesicles on Long-Term Stability and Their Response to Staphylococcus aureus and Pseudomonas aeruginosa Supernatants

Abstract: Phospholipid vesicles have been the focus of attention as potential vehicles for drug delivery, as they are biomimetic, easy to produce, and contain an aqueous compartment which can be used to carry hydrophilic material, such as drugs or dyes. Lipid vesicles used for this purpose present a particular challenge, as they are not especially stable and can rapidly break down and release their contents away from the target area, especially at physiological temperatures/environments. This study aims to investigate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Here we present a new methodology in detecting and quantifying RL using carboxylfluorescein encapsulated phospholipid vesicles. We have previously shown that these vesicles are stable under various conditions (Marshall et al 2013) and are susceptible to a suite of Stapylococcus aureus toxins that have surfactant-like properties (Laabei et al 2014b). In this report we confirm that RL can be detected and semi-quantified directly from pure overnight culture supernatants of P. aeruginosa using the vesicle-lysis assay, decreasing preparation time, hazardous extraction techniques or expert analysis.…”
Section: Introductionsupporting
confidence: 77%
“…Here we present a new methodology in detecting and quantifying RL using carboxylfluorescein encapsulated phospholipid vesicles. We have previously shown that these vesicles are stable under various conditions (Marshall et al 2013) and are susceptible to a suite of Stapylococcus aureus toxins that have surfactant-like properties (Laabei et al 2014b). In this report we confirm that RL can be detected and semi-quantified directly from pure overnight culture supernatants of P. aeruginosa using the vesicle-lysis assay, decreasing preparation time, hazardous extraction techniques or expert analysis.…”
Section: Introductionsupporting
confidence: 77%
“…22,23 This is accomplished through the use of synthetic lipid vesicles loaded with fluorescent self-quenching dye, which are sensitive to the key population-density regulated cytotoxic virulence factors produced by major wound pathogens 19,24,25 . These vesicles were found to be stable under conditions reflective of the un-infected wound environment, 26 but production of cytotoxins by bacterial pathogens results in lysis and dye release, which may be used to provide a clear signal that the CCT has been reached, and clinically relevant infection has been intiated. 19,24 The natural evolution of this technology is now the incorporation of vesicles directly within wound dressings, to produce "intelligent", infection-responsive, theranostic devices that can notify clinicians of the need to intervene directly at point of care.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, phospholipid vesicles contained within a hydrogel matrix have been demonstrated as potential antimicrobial delivery vehicles. 17 Potential opening mechanisms for the drug delivery systems include swelling of hydrogels, 18,19 environmental pH changes, 20 membrane lytic action of secretion toxins from the infecting bacteria, which open phospholipid vesicles, [21][22][23] or polymer degradation by extracellular enzymes. 24 Accordingly, biodegradable/compatible materials like polysaccharides seem very promising for such drug-delivery systems at the nanoscale as they can oen be degraded specically by bacterial enzymes.…”
Section: Introductionmentioning
confidence: 99%